Glioblastoma evolving within 10 days following unremarkable computer tomography of the brain: a case report. (3rd July 2021) - Schröter, Nils; Lützen, Niklas; Doostkam, Soroush; Berger, Benjamin
Abstract: Glioblastoma multiforme might develop radiologically within a few days following unremarkable CT scan of the brain. Glioblastoma multiforme is the most frequent primary brain tumor. Initial presentations are diverse, including headache, seizures and transient or persistent neurological deficits. Cerebral imaging followed by histological examination of a tissue specimen is the mainstay of diagnosis. We report the case of a 79-year-old female patient whose computer tomography (CT) of the brain was unremarkable at first clinical presentation with a transient hemiparesis of the right side, but revealed a cerebral space-occupying lesion ultimately diagnosed as glioblastoma only 10 days later. According to our case presentation glioblastoma might develop radiologically within a few days following unremarkable CT scan of the brain. Since clinical manifestation with a transient ischemic attack (TIA)-like episode was preceding CT manifestation, this case indicates, that a magnetic resonance imaging (MRI) should be routinely performed in all patients presenting with TIA.